2022
DOI: 10.3389/fpls.2022.853651
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Volatile Diversity Yield Insights Into the Genetics and Biochemistry of the Date Palm Fruit Volatilome

Abstract: Volatile organic compounds are key components of the fruit metabolome that contribute to traits such as aroma and taste. Here we report on the diversity of 90 flavor-related fruit traits in date palms (Phoenix dactylifera L.) including 80 volatile organic compounds, which collectively represent the fruit volatilome, as well as 6 organic acids, and 4 sugars in tree-ripened fruits. We characterize these traits in 148 date palms representing 135 varieties using headspace solid-phase microextraction gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…S3), which is distantly related to ItypOR6/DponOR8/HabiOR3. 2-PE has already been reported in palms 51 . It would be more interesting to know whether 2-PE is an antifeedant/deterrent in other curculionids and, thus, why RferOR2 detects it, which is tuned to attractants.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…S3), which is distantly related to ItypOR6/DponOR8/HabiOR3. 2-PE has already been reported in palms 51 . It would be more interesting to know whether 2-PE is an antifeedant/deterrent in other curculionids and, thus, why RferOR2 detects it, which is tuned to attractants.…”
Section: Discussionmentioning
confidence: 67%
“…Apart palm esters, we investigated whether RferOR2 detects other palm volatiles by including two key ketones (2-pentanone and acetoin) commonly reported as palm volatiles [49][50][51] . Our results showed that RferOR2 did not exclusively detect palm esters (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aroma and flavor comes from a complex mixture atile compounds. From the volatiloma of 135 varieties of dates, 80 volatile comp belonging to acids, alcohols, aldehydes, and esters, were described [41]. The most f variety of P. dactylifera is Majoul, which was first imported into the USA from M Instead, Ajwa variety dates can be distinguished from other date varieties due t…”
Section: Date Palm Characteristicsmentioning
confidence: 99%
“…Date fruits from P. dactylifera are much appreciated for their flavor, which has been extensively studied [41][42][43]. The aroma and flavor comes from a complex mixture of volatile compounds.…”
Section: Date Palm Characteristicsmentioning
confidence: 99%